Perlindungan Hukum terhadap Korban Penyalahgunaan Teknik Deepfake - Anfa’un Nisa’ Fidinir Rahman; Syariffudin Syariffudin; Fathol Bari (Perspektif Administrasi Publik dan hukum, 2025)
This research aims to find out the regulations regarding deepfake crimes in Indonesia and to find out the ideal regulations regarding deepfake crimes in the future. This technology, which is increasingly developing rapidly, can essentially make it easier to do anything. Apart from that, technological developments can cause serious problems, one of which is the misuse of deepfakes which are part of artificial intelligence. Deepfakes certainly harm many people, starting from victims whose identities are used by fraudsters, to victims who suffer material losses. The absence of regulations governing deepfakes means that state protection for victims of this crime is still in doubt. This research uses a normative legal research method which uses 3 (three) approaches, namely the statutory approach, the comparative approach and the conceptual approach. This research uses data collection techniques through library research. This research uses descriptive data analysis techniques by presenting data and information as a description of the research subjects and objects which are arranged systematically so that they can be understood. This research also uses a prescriptive analysis method, namely by providing arguments on the research results that have been described. The results of this research show that Indonesia has not yet explicitly regulated deepfake crimes. Indonesia only regulates falsification of personal data in general in the ITE Law which is a derivative of the 1945 Constitution of the Republic of Indonesia.